Primary hyperoxaluria type 2 and systemic oxalosis. A case report - Loza Munarriz, Reyner (2019)
Primary hyperoxaluria type 2 is a rare disease characterized by over production of oxalate due to a deficiency of an intra hepatic enzyme leading to renal lithiasis, nephrocalcinosis and chronic kidney damage. We report the case of 17-year-old male patients with history of urinary tract infections and renal lithiasis since the age of 6 years. The patient developed end-stage kidney disease at the age of 11 years receiving chronic ambulatory peritoneal dialysis. He developed back pain and polyarthralgia of the ankles, knees, shoulders and progressive deformity of the hands. The magnetic resonance of the spine revealed flattening of D9-D9. Bone biopsy of the affected area showed presence of calcium oxalate. A genetic study confirmed the diagnosis of primary hyperoxaluria type 2. This entity should be suspected in children with renal stones at an early age, this may be the first case in Peru.